THE ROLE OF TOLL-LIKE RECEPTORS IN UPPER RESPIRATORY TRACT INFECTIONS - DSc I. Yu. Mamatova; Phd O. K. Djalalova (Modern American Journals, 2025)
Upper respiratory tract infections (URTIs) are among the most common infectious diseases worldwide, caused primarily by viruses and, less frequently, by bacteria. Toll-like receptors (TLRs), as key components of the innate immune system, play a central role in recognizing pathogen-associated molecular patterns (PAMPs) and initiating immune responses in the respiratory epithelium. This article reviews the expression and function of TLRs in the upper respiratory tract, their involvement in pathogen detection, and the consequences of dysregulated TLR signaling. Understanding TLR-mediated mechanisms in URTIs may aid in developing novel immunomodulatory therapies.